2017
DOI: 10.37358/rc.17.4.5522
|View full text |Cite
|
Sign up to set email alerts
|

The Examination of the Effects of Relative Humidity on the Changes of Tropospheric Ozone Concentrations in the Ciuc Basin, Romania

Abstract: As ozone is a secondary polluting substance, its oxides of nitrogen (NOx) play a significant role as precursors. Their existence is influenced by climatological and meteorological parameters, as well as other air pollutants (SOA, VOC). At present, alongside with various meteorological parameters (temperature, wind speed, relative humidity, sun intensity), other air pollutants (oxides of nitrogen, carbon monoxide, benzene) and other physical phenomena (dry deposition, meteoric stability) mostly the indirect eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…-> H + , showing that the two most dominant ions were Lower evapotranspiration, due to groundwater drainage works conducted during the 60's and 70's, increased the static stability of the atmosphere, which caused longer thermal inversion episodes [27][28][29]. During these periods, the lack of vertical and/or horizontal mixing of air masses, can cause them to persist for days, limiting the dilution process of air pollutants in the basin, hence the accumulation of pollutants occurs [33,34]. Drainage works and the soil water decrease has led to the degradation of peaty and acidophilic soils, leading to changes in ecosystems, such as the appearance of invasive allochthone species [30].…”
Section: Resultsmentioning
confidence: 99%
“…-> H + , showing that the two most dominant ions were Lower evapotranspiration, due to groundwater drainage works conducted during the 60's and 70's, increased the static stability of the atmosphere, which caused longer thermal inversion episodes [27][28][29]. During these periods, the lack of vertical and/or horizontal mixing of air masses, can cause them to persist for days, limiting the dilution process of air pollutants in the basin, hence the accumulation of pollutants occurs [33,34]. Drainage works and the soil water decrease has led to the degradation of peaty and acidophilic soils, leading to changes in ecosystems, such as the appearance of invasive allochthone species [30].…”
Section: Resultsmentioning
confidence: 99%
“…Alrededor del mundo, se han llevado a cabo gran cantidad de estudios relacionados con la dinámica entre los NOX, el CO, el O3 troposférico y los parámetros meteorológicos. Frecuentemente, en las ciudades estudiadas se evidencia una relación directa entre las concentraciones de NOX y CO, debido a que estos gases son emitidos directamente por el parque automotor, e inversa entre los niveles de ambos contaminantes y la concentración de O3 troposférico, pues estos funcionan como sus precursores (Roberts-Semple et al, 2012;Kovač-Andrić et al, 2013;Tumwitike et al, 2014;Kalbarczyk et al, 2015;Szep et al, 2016;Wang et al, 2019). La temperatura del aire y la radiación solar suelen tener una relación directa con las concentraciones de O3 troposférico e inversa con las de NOX y CO, ya que tales parámetros meteorológicos fomentan las reacciones de formación del O3 troposférico y, por lo mismo, el consumo de sus precursores (es decir, de contaminantes como los NOX y el CO) (Ocak & Turalioglu, 2008;Kalbarczyk et al, 2015;Szep et al, 2016;Gasmi et al, 2017).…”
Section: Introductionunclassified
“…Frecuentemente, en las ciudades estudiadas se evidencia una relación directa entre las concentraciones de NOX y CO, debido a que estos gases son emitidos directamente por el parque automotor, e inversa entre los niveles de ambos contaminantes y la concentración de O3 troposférico, pues estos funcionan como sus precursores (Roberts-Semple et al, 2012;Kovač-Andrić et al, 2013;Tumwitike et al, 2014;Kalbarczyk et al, 2015;Szep et al, 2016;Wang et al, 2019). La temperatura del aire y la radiación solar suelen tener una relación directa con las concentraciones de O3 troposférico e inversa con las de NOX y CO, ya que tales parámetros meteorológicos fomentan las reacciones de formación del O3 troposférico y, por lo mismo, el consumo de sus precursores (es decir, de contaminantes como los NOX y el CO) (Ocak & Turalioglu, 2008;Kalbarczyk et al, 2015;Szep et al, 2016;Gasmi et al, 2017). Asimismo, es común observar una dinámica opuesta entre la humedad relativa y estos gases en comparación con la de la temperatura del aire, puesto que la humedad relativa suele disminuir conforme la temperatura del aire asciende (Wallace & Kanaroglou, 2009); y dado que niveles altos de humedad relativa suelen indicar una alta inestabilidad atmosférica, alta abundancia de nubes y mayor intensidad de deposición húmeda, lo cual se relaciona a su vez con menores niveles de O3 troposférico (Liu et al, 2020;Zoran et al, 2020).…”
Section: Introductionunclassified
“…Studies have shown, that the response of plants to air pollutants is influenced by the relationship between ascorbic acid levels and ozone susceptibility from different geospheres [3]. Ozone has a high oxidative potential, causing crop yield reductions, and also influencing the chemical composition of precipitation [4][5][6][7][8][9][10].…”
mentioning
confidence: 99%